2006
DOI: 10.1007/s11240-005-9071-1
|View full text |Cite
|
Sign up to set email alerts
|

Embryo rescue and plant regeneration in vitro of selfed chickpea (Cicer arietinum L.) and its wild annual relatives

Abstract: The main constraint to the transfer of desired traits into cultivated chickpea from wild Cicer relatives is the presence of post-zygotic barriers which result in abortion of the immature embryo following interspecific hybridisation. Rescue of hybrid embryos in vitro and regeneration of hybrid plantlets could allow chickpea breeders to transfer desirable traits from wild relatives of chickpea. The development of embryo rescue techniques using selfed chickpea and selfed wild relatives is being used as a first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Embryo abortion is another important factor related to fecundity (Mont et al 1993;Singh 1998;Mallikarjuna and Saxena 2002;Datson et al 2006). For instance, Clarke et al (2006) reported that the main constraint of the transfer of desired traits into cultivated chickpea from wild Cicer relatives was the presence of post-zygotic barrier, i.e., abortion of the immature embryos. Similarly, Ndoutoumou et al (2007) found that embryo abortion after fertilization was the main factor causing failure of the cross between Phaseolus vulgaris and P. coccineus.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo abortion is another important factor related to fecundity (Mont et al 1993;Singh 1998;Mallikarjuna and Saxena 2002;Datson et al 2006). For instance, Clarke et al (2006) reported that the main constraint of the transfer of desired traits into cultivated chickpea from wild Cicer relatives was the presence of post-zygotic barrier, i.e., abortion of the immature embryos. Similarly, Ndoutoumou et al (2007) found that embryo abortion after fertilization was the main factor causing failure of the cross between Phaseolus vulgaris and P. coccineus.…”
Section: Discussionmentioning
confidence: 99%
“…Successful hybridizations between the cultivated chickpea and C. reticulatum or C. echinospermum and their reciprocals have been reported (Ladizinsky and Adler, 1976ab;Jaiswal and Singh, 1986;Singh and Ocampo, 1993;Croser et al, 2003;Ahmad and Slinkard, 2004;Singh et al, 2005;Clarke et al, 2006;Knights et al, 2008;Malikarjuna et al, 2011;Thompson et al, 2012). Although some of the accessions of C. bijugum, C. judaicum and C. pinnatifidum used as pollen donors were crossed with the cultivated chickpea, hybrids were available via embryo rescue techniques (Ahmad and Slinkard, 2004).…”
Section: Wild Relatives As a Source Of Novelmentioning
confidence: 99%
“…Rescuing and culturing younger embryos when they are not readily visible may require the inclusion of other tissue such as embryo sac and even part of the ovary. Likewise, parental genetic, phenological and physiological differences can also contribute to variations in the in vitro responses of rescued embryos (Clarke et al, 2006).…”
Section: Resultsmentioning
confidence: 99%